Delay constraint minimum interruption routing algorithm for mobile satellite network - ZHANG Tao; LIU Zhong-kan; ZHANG Jun (Tongxin xuebao)
By the analysis of the characteristics of mobile satellite network,such as a long delay and a topological time-varying,a novel satellite network delay constraint optimal path（SDCOP）algorithm,which could obtain a path to sat-isfy the delay constraint condition as well as the minimization of interruption during the service,was proposed.This algo-rithm exploits the predictive nature of connectivity changes of time-varying topological to decrease the influence in the QoS routing performance caused by the handover.Besides,it has a low computing complexity to adapt to the restricted computing capability of satellite equipments.Correlative simulation indicates that this novel algorithm is superior to other current algo-rithm in respect of computing complexity,service blocking probability and interrupting probability etc.